Mitoxantrone Therapy for Acute Posterior Multifocal Placoid Pigment Epitheliopathy with Cerebral Vasculitis - Hélène Massé; Jean-Laurent Guyomard; Dominique Baudet; Jean-François Pinel; Gilles Edan; Jean-François Charlin (Case Reports in Medicine)
Purpose. To report favorable outcome of a case of acute posterior multifocal placoid pigment epitheliopathy (APMPPE) associated with cerebral vasculitis after treatment with immunosuppressive therapy by mitoxantrone. Design. Single case report. Method. A 22-year-old man presented with acute isolated bilateral loss of vision revealing APMPPE. Corticosteroid therapy was initiated and visual acuity gradually improved. Seventeen days later, visual function deteriorated again, associated with flu-like syndrome and severe headaches. A relapse of APMPPE was diagnosed, complicated with lymphocytic meningitis and cerebral ischemia. Intravenous therapy with mitoxantrone was performed in combination with methylprednisolone. Results. Headaches disappeared in a few days whereas visual acuity gradually improved and stabilized at 20/40 in the right eye and 20/32 in the left eye. No adverse event was observed. Clinical improvement was confirmed by magnetic resonance imaging. Conclusion. Cerebral vasculitis is the most severe complication of the extraocular manifestations of APMPEE. This diagnosis should be evoked when severe headaches or behavior disorder are associated with APMPEE.